Advancing the Thermal Network Representation for the Optimal Design of Distributed Multi-Energy Systems - Wang, Danhong; Li, Xiang; Marquant, Julien; Carmeliet, Jan; Orehounig, Kristina (Frontiers in Energy Research, 2021)
This paper investigates modeling methods with thermal network representation under the scope of the optimal design and operation of Distributed Multi-Energy System (D-MES). Two modeling approaches are compared: A Mixed‐Integer Linear Programming (MILP) optimization model and a district heating network (DHN) simulation model. The MILP model was developed for the simultaneous design of the network layout, the sizing, and locations of energy generation and storage technologies to minimize both costs and carbon emissions. The thermal network is represented with a simplified linear approximation. The DHN simulation model is a thermal-hydraulic model to address the non-linear operational performance regarding hourly heat losses, pumping energy, and temperature distribution along with the network. The discrepancies in the network’s costs and operational performances from the two models are identified. The MILP model is further improved by adding new constraints. Results from both MILP models are compared and demonstrated with a case study. It reveals that the state-of-art MILP-model with simplified network representation suffices for optimal selection and sizing for most of the technologies. Although more computationally intensive, the refined model can address the operational issues with distributed design solutions.